PENGARUH KREDIT USAHA RAKYAT (KUR) MIKRO BANK BRI DAN FAKTOR PRODUKSI LAIN NYA TERHADAP PRODUKSI PADA USAHA TANI NANAS DI KECAMATAN TANGKIT BARU KABUPATEN MUARO JAMBI - Hikmah, Sri; Alamsyah, Zulkifli; Rosyani, Rosyani (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to 1) determine the description of pineapple farming 2) analyze the effect of people's business credit (KUR) on pineapple farming production in Sungai Gelam District, Muaro Jambi Regency. The data used in this study are primary data and secondary data. The analysis method used is the classical assumption test based on ordinary least square and path analysis. The percentage ratio of the amount of KUR to the total cost per hectare of pineapple farming is 210.3%, this indicates that the use of the amount of KUR loans by farmers exceeds the total cost of pineapple farming in one harvest season. The amount of KUR is too large for the total cost of farming of IDR 6,644,737 per hectare. The results of the study indicate that the variables that are significant in the use of production are the variables of land area and People's Business Credit (KUR).